CRITICAL THINKING IN ISLAMIC EDUCATION: DEVELOPING A PEDAGOGICAL FRAMEWORK FOR PROMOTING ANALYTICAL SKILLS AMONG STUDENTS - Saepudin, Aep (Ikatan Dosen Menulis, 2022)
Critical thinking is an essential skill in modern education, fostering the ability to analyze, evaluate, and synthesize information in a reflective and logical manner. In the context of Islamic education, promoting critical thinking is crucial for developing students' analytical skills and preparing them to navigate complex religious, social, and ethical issues. This study aims to develop a pedagogical framework that integrates Islamic educational principles with contemporary strategies for enhancing critical thinking among students. Through a systematic literature review and qualitative analysis of existing educational practices, this research identifies key components of an effective framework for fostering analytical skills. The findings highlight the importance of incorporating reflective questioning, active learning, and collaborative problem-solving into the curriculum. Additionally, the study underscores the role of teachers in modeling critical thinking and creating an environment conducive to open inquiry and intellectual growth. The proposed framework offers practical guidelines for educators seeking to enrich their teaching practices and enhance students' critical thinking abilities. The implications of this study extend to curriculum development, teacher training, and educational policy, emphasizing the need for a holistic approach to integrating critical thinking in Islamic education. Future research should explore the implementation of this framework in diverse educational settings and assess its impact on student outcomes.